PELATIHAN PEGEMBANGAN INSTRUMEN PEMBELAJARAN SD - Sundahry Sundahry; Dhini Mufti; Opi Andriani; Yelvia Prahagia; Jeni Mardiana (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
This community service program is motivated by the teacher's obligation to prepare learning tools including test questions that will be given to students. The preparation of the question text must be accompanied by a question grid so that the questions used are in accordance with the criteria. Therefore, the Muhammadiyah Muara Bungo University service team conducted training on drafting the question papers along with the question papers for the teachers. Community service activities use practical methods by providing training and mentoring in writing questions and making questions. Workshop activities are delivered in the meeting room provided by the school. All teachers at the school where the dedication took place took part in the activity. The method used: Lectures, Discussions, and Giving Assignments. The results obtained in the implementation of this community service activity are that the teacher is able to compile and make a grid of questions and the preparation of questions that can be used to measure the assessment of student learning outcomes.